2005
DOI: 10.1073/pnas.0505020102
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects in unirradiated human tissue induced by radiation damage up to 1 mm away

Abstract: A central tenet in understanding the biological effects of ionizing radiation has been that the initially affected cells were directly damaged by the radiation. By contrast, evidence has emerged concerning ''bystander'' responses involving damage to nearby cells that were not themselves directly traversed by the radiation. These long-range effects are of interest both mechanistically and for assessing risks from low-dose exposures, where only a small proportion of cells are directly hit. Bystander effects have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
166
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(181 citation statements)
references
References 44 publications
9
166
1
Order By: Relevance
“…First, it could be possible that the level of DSBs in the neighboring cells affects the efficiency of repair [i.e., a cell may not repair its break when the neighboring cells are devoid of any DSBs (which is the case after 10 mGy and below) but may show efficient repair if all cells of a population harbor a break (at 40-80 mGy and above)]. Such an explanation would require an intercellular communication or bystander mechanism, which has been reported for cells and tissues (35). However, to date, we have no solid evidence that a bystander-like mechanism underlies the inefficient repair at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…First, it could be possible that the level of DSBs in the neighboring cells affects the efficiency of repair [i.e., a cell may not repair its break when the neighboring cells are devoid of any DSBs (which is the case after 10 mGy and below) but may show efficient repair if all cells of a population harbor a break (at 40-80 mGy and above)]. Such an explanation would require an intercellular communication or bystander mechanism, which has been reported for cells and tissues (35). However, to date, we have no solid evidence that a bystander-like mechanism underlies the inefficient repair at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Several multicellular tissue models summarised in table 2, have been used to investigate RIBEs ex vivo using sections of porcine ureter (26,27) and reconstructed 3D skin models (28,29). Recently, Sheridan et al, (31) observed RIBEs manifest as elevated DNA damage in nonadjacent colon tissue obtained from patients receiving post neoadjuvant radiotherapy.…”
Section: New Experimental Approaches For Studying Ribesmentioning
confidence: 99%
“…Three-dimensional models can reproduce many of the tissue characteristics in vivo (Griffith and Swartz 2006) and are therefore ideal targets in microbeams for studying non-targeted effects. So far, mostly skin constructs have been used at microbeams (Belyakov et al 2005;Sedelnikova et al 2007;Schmid et al 2010;Miller et al 2011), but new organotypic slice culture methods offer the possibility of irradiating parts from all kinds of human tissues and to study their late response (Merz et al 2010). The tissue models at microbeams can be very useful to clarify the role of cell signaling and tissue remodeling in radiation response.…”
Section: Tissue and Animal Modelsmentioning
confidence: 99%